Perancangan Sistem Informasi Administrasi Home Stay Palanta Roemah Kajoe Berbasis Web - Rezki Amelia (Ekasakti Jurnal Penelitian dan Pengabdian, 2025)
Palanta Roemah Kajoe Homestay in Padang City faces challenges in managing reservation administration, which is still conducted manually, leading to risks such as data entry errors, delayed services, and potential overbooking. This study aims to design a web-based administrative information system to improve the efficiency and effectiveness of reservation processes and data management. The system development method used is the System Development Life Cycle (SDLC) with a waterfall model, consisting of analysis, design, implementation, and testing phases. The system was designed using Unified Modeling Language (UML) and implemented using the PHP programming language and MySQL database. The results indicate that the developed system successfully automates reservation processes, provides real-time information, and facilitates administrators in generating financial reports and managing room availability digitally. In conclusion, the information system offers an effective solution to administrative problems in homestay management and supports the digital transformation of accommodation-based SMEs.